2010
DOI: 10.1007/s00404-010-1655-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and predictive value of CA-125 regression during neoadjuvant chemotherapy for advanced ovarian or primary peritoneal carcinoma

Abstract: CA-125 regression rate during pre-operative NAC is of independent prognostic value. CA-125 regression rate strongly predicts for optimal cytoreduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…In our study we manifested the usefulness of CA 125 in predicting the need of the neoadjuvant chemotherapy in a selected group of patients with advanced ovarian cancer. The area under the curve (AUC) for CA 125 was 0.833 for the entire study group and 0.793 for the serous carcinomas group which is consistent with studies carried out by Vasudev et al [22]. We also showed a statistically significant difference in baseline values of CA 125 among a group of women undergoing the primary surgery followed by the neoadjuvant chemotherapy and between the sensitive and resistant patients to platinum analogues.…”
Section: Discussionsupporting
confidence: 90%
“…In our study we manifested the usefulness of CA 125 in predicting the need of the neoadjuvant chemotherapy in a selected group of patients with advanced ovarian cancer. The area under the curve (AUC) for CA 125 was 0.833 for the entire study group and 0.793 for the serous carcinomas group which is consistent with studies carried out by Vasudev et al [22]. We also showed a statistically significant difference in baseline values of CA 125 among a group of women undergoing the primary surgery followed by the neoadjuvant chemotherapy and between the sensitive and resistant patients to platinum analogues.…”
Section: Discussionsupporting
confidence: 90%
“…(Mw < 2000 kDa) and the lack of suitable antibodies for this procedure have posed as a significant analytical limitation that will be addressed in future studies. Even though this is the first report regarding MUC16 expression in bladder cancer, CA125 elevation has been previously observed in the serum of patients with advanced pathological stage in comparison with lowerstage disease, suggesting that this antigen may predict advanced bladder cancer (Margel et al, 2007;Vasudev et al, 2011). Furthermore, abnormal CA125 levels have been associated with unresectable tumours, again reinforcing its association with worse prognosis (Vasudev et al, 2011).…”
Section: Bladder Cancer-targeted Glycoproteomicsmentioning
confidence: 56%
“…The CA 125 cut-off value used by Rodriguez et al 16 was substantially greater than that of the present study because Rodriguez et al 16 included a median of 3 courses of NACT, whereas our study included a median of 6 courses. Vasudev et al 18 reported that the regression rate of serum CA 125 levels during NACT had both prognostic and predictive value. However, our results do not support these prior findings, because we observed that the number of NACT courses required for serum CA 125 levels to halve or reduce to <35 U/mL was similar between the optimal/complete and the suboptimal surgery groups.…”
Section: Discussionmentioning
confidence: 99%